Synthesis and crosslinking reaction of polyacetylenes substituted with benzoxazine rings: Thermally highly stable benzoxazine resins. Issue 16 (24th August 2018) - Goto, Masahide; Miyagi, Yu; Minami, Masaki; Sanda, Fumio
ABSTRACT: Novel polyacetylenes, poly(1 ) and poly(2 ) substituted with benzoxazine rings were synthesized by the polymerization of the corresponding acetylene monomers1 and2 using Rh catalysts, [(nbd)RhCl]2, and (nbd)Rh + B – Ph4 (nbd = 2, 5‐norbornadiene). The polymers were heated at 250 °C under N2 to obtain the corresponding polybenzoxazine resins, poly(1 )′ and poly(2 )′ possessing polyacetylene main chains via the ring‐opening polymerization of the benzoxazine moieties. The polyacetylene backbones were maintained after crosslinking reaction at 250 °C, which were confirmed by Raman spectroscopy. The benzoxazine resins were thermally highly stable as evidenced by differential scanning calorimetry and thermogravimetric analysis. The surface of poly(1 )′ film became hydrophilic compared to that of poly(1 ), while the surfaces of poly(2 ) and poly(2 )′ films showed almost the same hydrophilicity judging from the water contact angle measurement. Poly(1 )′ and poly(2 )′ exhibited refractive indices smaller than those of poly(1 ) and poly(2 ). © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1884–1893 Abstract : Polyacetylenes substituted with benzoxazine rings were synthesized by the polymerization of the corresponding acetylene monomers. The polymers underwent ring‐opening crosslinking at the benzoxazine moieties at 250 °C to give rise to resins with the polyacetylene backbone intact. The resins were thermally highly stable as evidenced by DSC and TGA.